2011
DOI: 10.1051/0004-6361/201116971
|View full text |Cite
|
Sign up to set email alerts
|

Long-term magnetic activity of a sample of M-dwarf stars from the HARPS program

Abstract: Context. The search for extra-solar planets similar to Earth is becoming a reality, but as the level of the measured radial-velocity reaches the sub-m s −1 , stellar intrinsic sources of noise capable of hiding the signal of these planets from scrutiny become more important. Aims. Other stars are known to have magnetic cycles similar to that of the Sun. The relationship between these activity variations and the observed radial-velocity is still not satisfactorily understood. Following our previous work, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(176 citation statements)
references
References 54 publications
9
164
2
Order By: Relevance
“…This index is defined as the ratio between the flux in the Hα absorption line and that in the surrounding continuum, as described in Boisse et al (2011). We use a 0.16 nm window centered at 656.2808 nm for the central line, and two windows of 1.075 and 0.875 nm around 655.087 and 658.031 nm respectively for the continuum as presented in Gomes Da Silva et al (2011).…”
Section: Computing Rvs and Activity Proxiesmentioning
confidence: 99%
“…This index is defined as the ratio between the flux in the Hα absorption line and that in the surrounding continuum, as described in Boisse et al (2011). We use a 0.16 nm window centered at 656.2808 nm for the central line, and two windows of 1.075 and 0.875 nm around 655.087 and 658.031 nm respectively for the continuum as presented in Gomes Da Silva et al (2011).…”
Section: Computing Rvs and Activity Proxiesmentioning
confidence: 99%
“…We suspected that this behaviour was due to activity or rotation and did a a posteriori study of the impact of the activity with our technique. To this end, we used the normalised Hα luminosity, log L H α /L bol , from Reiners et al (2012), for the stars in common with our full sample, as well as the median of individual measurements of the H α index defined by Gomes da Silva et al (2011), kindly provided by the author. Table 4 lists both activity indicators, in Cols.…”
Section: A Posteriori Sample Selectionmentioning
confidence: 99%
“…2 and 3, the right ascension and declination of the star, respectively. Column 4 depicts the S/N, Col. 5 the normalised Hα index taken from Reiners et al (2012), and Col. 6 the Hα index described by Gomes da Silva et al (2011). Column 7 shows the metallicity calculated with the coefficient matrix used in our previous work, Neves et al (2013), Col. 8 the [Fe/H] obtained in our work, along with its associated error in Col. 9.…”
Section: Testing Our Technique As a Function Of Resolution And S/nmentioning
confidence: 99%
“…Gomes da Silva et al (2011) concluded that H α shows good correlation with S Ca II for the most active stars, indicating that the correlation between Ca II and H α depends on the activity level of the star. The correlation between different activity indicators is complex and can be different depending on the star (Cincunegui et al 2007; see also Meunier & Delfosse 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors explained such observations by means of theoretical modelling (Saar & Donahue 1997;Hatzes 2002;Desort et al 2007). On the other hand, the impact of solar-like activity cycles on high-precision RVs has been studied only recently by analysing the correlations between observed jitter and chromospheric activity for the stars in the California Planet Search (Isaacson & Fischer 2010) or by computing chromospheric activity indicators based on some element lines as in the HARPS program (Gomes da Silva et al 2011). Some authors proposed several methods and models to reduce the associated noise Meunier & Lagrange 2013) and predict the activity-induced RV variations (Lanza et al 2011).…”
Section: Introductionmentioning
confidence: 99%